Enzymatically modified starch up-regulates expression of incretins and sodium-coupled monocarboxylate transporter in jejunum of growing pigs. (8th December 2016) - Metzler-Zebeli, B. U.; Ertl, R.; Grüll, D.; Molnar, T.; Zebeli, Q.
Abstract : Dietary effects on the host are mediated via modulation of the intestinal mucosal responses. The present study investigated the effect of an enzymatically modified starch (EMS) product on the mucosal expression of genes related to starch digestion, sugar and short-chain fatty acid (SCFA) absorption and incretins in the jejunum and cecum in growing pigs. Moreover, the impact of the EMS on hepatic expression of genes related to glucose and lipid metabolism, and postprandial serum metabolites were assessed. Barrows ( n =12/diet; initial BW 29 kg) were individually fed three times daily with free access to a diet containing either EMS or waxy corn starch as control (CON) for 10 days. The enzymatic modification led to twice as many α -1, 6-glycosidic bonds ( 8%) in the amylopectin fraction in the EMS in comparison with the non-modified native waxy corn starch (4% α -1, 6-glycosidic bonds). Linear discriminant analysis revealed distinct clustering of mucosal gene expression for EMS and CON diets in jejunum. Compared with the CON diet, the EMS intake up-regulated jejunal expression of sodium-coupled monocarboxylate transporter ( SMCT ), glucagon-like peptide-1 ( GLP1 ) and gastric inhibitory polypeptide ( GIP ) ( P <0.05) and intestinal alkaline phosphatase ( ALPI ) ( P =0.08), which may be related to greater luminal SCFA availability, whereas cecal gene expression was unaffected by diet. Hepatic peroxisome proliferator-activated receptor γ ( PPARγ ) expression tended ( P =0.07) to be down-regulated in pigs fed the EMS diet compared with pigs fed the CON diet, which may explain the trend ( P =0.08) of 30% decrease in serum triglycerides in pigs fed the EMS diet. Furthermore, pigs fed the EMS diet had a 50% higher ( P =0.03) serum urea concentration than pigs fed the CON diet potentially indicating an increased use of glucogenic amino acids for energy acquisition in these pigs. Present findings suggested the jejunum as the target site to influence the intestinal epithelium and altered lipid and carbohydrate metabolism by EMS feeding.